2014
DOI: 10.1094/cchem-10-13-0211-r
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Elevated Nighttime Air Temperatures During Kernel Development on Starch Properties of Field‐Grown Rice

Abstract: Cereal Chem. 91(4):350-357The structural features of starch were examined to better understand the causes of variability in rice quality resulting from nighttime air temperature (NTAT) incidence during kernel development. Starch samples were isolated from head rice of four cultivars (Bengal, Cypress, LaGrue, and XL723) field-grown in four Arkansas locations (Keiser, Pine Tree, Rohwer, and Stuttgart) in 2009 and 2010. Average NTATs recorded during the grain-filling stages of rice reproductive growth in the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…Pasting temperature was increased by heat stress at the early (1–5 DAP) and late (11–15 DAP) stages but was not influenced by heat stress applied to the mid grain formation stage. Patindol et al . observed that higher night temperatures increased the starch peak, trough, final and breakdown viscosities, and decreased the setback viscosity of rice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pasting temperature was increased by heat stress at the early (1–5 DAP) and late (11–15 DAP) stages but was not influenced by heat stress applied to the mid grain formation stage. Patindol et al . observed that higher night temperatures increased the starch peak, trough, final and breakdown viscosities, and decreased the setback viscosity of rice.…”
Section: Resultsmentioning
confidence: 99%
“…Song et al . and Patindol et al . observed that rice starch crystallinity was increased by higher night‐time temperatures during grain filling owing to increase in proportion of long glucan chains in amylopectin.…”
Section: Resultsmentioning
confidence: 99%
“…7B), wherein AAC is loaded together with FV, SB, and TSB on the fourth quadrant, whereas BD was positioned oppositely on the second quadrant. The significant impact of amylose content on rice pasting characteristics has been extensively studied and reported by various authors (Patindol and Wang 2002; Bao et al 2007; Cameron et al 2007; Park et al 2007; Li et al 2008; Patindol et al 2009, 2014; Chávez‐Murillo et al 2011; Kong et al 2015). Present findings on AAC–pasting property relationships are in agreement with the literature, except that AAC did not correlate with PV.…”
Section: Resultsmentioning
confidence: 99%
“…As tools for starch research have become more sophisticated, and the relevance of rice as a cereal crop continues to increase, the literature has also become more plentiful with articles reporting the impact of G × E effects on rice starch composition and properties; a summary of which is given in Table . These works examined the various aspects of starch in milled rice: fine structure ; amylose and other chemical contents ; pasting, gelatinization, and retrogradation behavior ; milling yields and milled rice appearance ; and cooking and sensory characteristics . Amylose content was the most frequently used, starch‐related quantitative trait as it is also the most widely used indicator of rice grain quality.…”
Section: Genotype–environment Effects On Starch Structurementioning
confidence: 99%